Efficacy and safety of ketamine for neonatal refractory status epilepticus: case report and systematic review - Pin, Jacopo Norberto; Leonardi, Letizia; Nosadini, Margherita; Cavicchiolo, Maria Elena; Guariento, Chiara; Zarpellon, Anna; Perilongo, Giorgio; Raffagnato, Alessia; Toldo, Irene; Baraldi, Eugenio; Sartori, Stefano (Frontiers in Pediatrics, 2023)
Background. Evidence-based data on treatment of neonatal status epilepticus (SE) are scarce. We aimed to collect data on the efficacy and safety of ketamine for the treatment of neonatal SE and to assess its possible role in the treatment of neonatal SE. Methods. We described a novel case and conducted a systematic literature review on neonatal SE treated with ketamine. The search was carried out in Pubmed, Cochrane, Clinical Trial Gov, Scopus and Web of Science. Results. Seven published cases of neonatal SE treated with ketamine were identified and analyzed together with our novel case. Seizures typically presented during the first 24 hours of life (6/8). Seizures were resistant to a mean of five antiseizure medications. Ketamine, a NMDA receptor antagonist, appeared to be safe and effective in all neonates treated. Neurologic sequelae including hypotonia and spasticity were reported for 4/5 of the surviving children (5/8). 3/5 of them were seizure free at 1-17 months of life. Discussion. Neonatal brain is more susceptible to seizures due to a shift towards increased excitation because of a paradoxical excitatory effect of GABA, a greater density of NMDA receptors and higher extracellular concentrations of glutamate. Status epilepticus and neonatal encephalopathy could further enhance these mechanisms, providing a rationale for the use of ketamine in this setting. Conclusions. Ketamine in the treatment of neonatal SE showed a promising efficacy and safety profile. However, further in-depth studies and clinical trials on larger populations are needed.